LOCAL ELECTIONS IN THE REPUBLIC OF SERBIA, 17TH DECEMBER 2023. (Heritage, 2024)
The aim of this work is the analysis of local elections in the Republic of Serbia, which, along with the national, parliamentary and provincial elections in Vojvodina, were held in 66 cities, municipalities and urban municipalities in central Serbia. The above-mentioned local elections were largely held at the initiative of the ruling party - SNS, and were called after early resignations of local leaders - in Belgrade under the strong pressure from a large part of the opposition public and in the other local self-governments they were held probably because of expetation of achieving very good results in specific local goverments. These elections were an opportunity to measure the political strength of the ruling parties and the opposition from the national level, as well as minority parties and groups of citizens and local movements. Exceptional political dynamics in Serbia were also shown in these elections, and their full resolution was not achieved even months after they were held, but this election cycle was also an introduction to new political tensions and additional polarization, primarily in the capital, Belgrade.
Keywords: local elections, political parties, citizens groups, local representation, local coalitions